IN UTERO EXPOSURES AND ENDOMETRIOSIS, THE ENDO STUDY - Wolff, Erin Foran (2012)
OBJECTIVE: To assess in utero exposures and the odds of an endometriosis diagnosis. DESIGN: Matched cohort design. SETTING: Fourteen participating clinical centers in geographically defined areas in Utah and California. STUDY COHORTS: The operative cohort comprised 473 women undergoing laparoscopy/laparotomy, and was matched on age and residence to a population cohort comprising 127 women undergoing pelvic magnetic resonance imaging (MRI), 2007–2009. INTERVENTIONS: None MAIN OUTCOME MEASURES: Women completed standardized interviews prior to surgery or MRI regarding in utero exposures: mothers’ lifestyle during the index pregnancy, and the index woman’s gestation and birth size. Endometriosis was defined as visually confirmed disease in the operative cohort, and MRI visualized disease in the population cohort. The odds of an endometriosis diagnosis and corresponding 95% confidence intervals (AOR; 95% CI) were estimated for each exposure by cohort using logistic regression and adjusting for current smoking, age at menarche, body mass index, and study site. RESULTS: Endometriosis was diagnosed in 41% and 11% of women in the operative and population cohorts, respectively. In the primary analysis, AORs were elevated for maternal vitamin usage (1.27; 95% CI =0.85–1.91), maternal cigarette smoking (1.16; 95% CI=0.61–2.24), and low birth weight (1.1; 95% CI=0.92–1.32). Reduced odds were observed for maternal usage of caffeine (0.99; 95% CI=0.64–1.54), alcohol (0.82; 95% CI=0.35–1.94), paternal cigarette smoking (0.72; 95% CI=0.43–1.19) and preterm delivery (0.98; 95% CI=0.47–2.03). Sensitivity analyses mostly upheld the primary results except for a decreased AOR for preterm birth (0.41; 95% CI=0.18–0.94) when restricting to visualized and histologically-confirmed endometriosis in the operative cohort. CONCLUSIONS: In utero exposures were not significantly associated with the odds of an endometriosis diagnosis in either cohort.